Sequential Exporting across Countries and Products - Facundo Albornoz; Héctor F. Calvo Pardo; Gregory Corcos; Emanuel Ornelas (Center for Economic Studies and Ifo Institute (CESifo), 2021)
How do exporters expand their product scope and geographical presence? We argue that new exporters are uncertain about their profitability in different countries and products, but learn it as they start to export. As a consequence, exporters add products and countries sequentially, in an interdependent process. Exploiting disaggregated data on French exporters, we find empirical support consistent with such a mechanism, where firms learn from their initial export experiences and then adjust their sales, number of products and destination countries accordingly. Our results indicate that part of the learning is firm-specific, and not merely product- or market-specific. Furthermore, we find that firms tend to expand in the sub-extensive margin first by widening product scope within a destination and later by entering new destinations; and that firms' core products are particularly resilient despite being used to “test the waters” when entering additional countries.
Keywords: F10; F14; D22; L25; 330; export dynamics; experimentation; uncertainty; multiproduct firms; market interdependence